Default in Sea Transportation Agreement - Hetharie, Yosia (Law Research Review Quarterly, 2020)
Transportation has a very important role in facilitating the mobilization of goods and or people at home and abroad, one of which is by sea. However, in its implementation for agreements to transport people (passengers) by sea, it often creates problems where passengers as consumers who use sea transportation services do not get their right to a seat even though they have bought a boat ticket according to the ticket price determined by the sea transportation company. The carrier action can be categorized as a default. Default (broken promise or negligence) is the failure to fulfill the performance of one of the parties as specified in the agreement. One form of default in the transportation agreement occurs when the carrier does not carry out his obligations to the passenger according to the evidence of the agreement in the form of a ticket that is sold to the passenger, which results in the passenger experiencing a loss by not feeling comfort and safety on the ship. Therefore, the carrier is fully responsible for losses suffered by passengers.